SOCIAL MEDIA INFLUENCES TO TEENAGERS - Dr. Cherry Nuñez-Rola & Dr. Niña Jen Ruta-Canayong (International Journal of Research Science and Management, 2019)
This paper analyzes discursively the influences of social media to teenagers. The theme and language of social media contents and the behavioral influences for social media awareness are specifically analyzed. The findings reveal that social media contents depict human frailties while internet slang mobilizes the contextual language of social media and teenagers’ use of social media critically influences internet addiction, sleeping pattern, communication preference, language acquisition, academic endeavor, task performance, and need for immediacy. Based on these results, it is concluded that social media drive the formation of the high school students’ behavior. Out of the findings and conclusion, the following are recommended: there be a guideline in choosing social media contents used as classroom teaching materials; the academe holistically assesses the effectiveness of social media as a communication channel and as a tool to enhance learning; and interventions to control social media use be considered by the different affected groups.